Gender predilection of congenitally missing teeth - MUTHUKUMAR, AARTHI; S, GHEENA.; SANDEEP, ADIMULAPU HIMA (The journal of contemporary issues in business and government, 2021)
Hypodontia or tooth agenesis is the most prevalent craniofacial malformation in humans. A tooth is considered to be congenitally missing when it remains invisible in radiographs and fails to erupt into the oral cavity. A thorough knowledge on tooth agenesis and its associated syndromes is essential as these are commonly encountered clinical scenarios. The aim of this study is to assess the current prevalence of dental agenesis in the permanent dentition among the patients visiting Saveetha Dental College.We reviewed 86000 patient records between. February 2019 to february 2020 and arrived at the data of 24. Cross verification of data is done by photographic and radiographic verification. Internal and external validity of the study were verified. Patients' details such as name , age , gender, missing teeth and treatment done were tabulated and transferred to SPSS software version 26 by IBM. The data is verified by 2 reviewers.The results of the study observed a male predilection for dental agenesis. And the most common missing teeth is maxillary lateral incisors.